Exploring Gender Representation in Class 12 English Textbook used in Schools - Luther DBP Simatupang; Rusdi Noor Rosa; Eddi Setia; Rahmadsyah Rangkuti (Jurnal Pendidikan Bahasa Inggris undiksha, 2024)
Balanced representation of gender characters in English textbooks, especially in Senior High School, has become a hot topic nowadays, because textbooks not only teach about science but also instill socio-cultural ideologies, norms, and values into students. Therefore, the purpose of this study is to analyze the ratio of how men and women are represented in various contexts in textbooks for grade 12 of Senior High School. This study uses qualitative descriptive for critical analysis of images as a method to see the appearance of men and women in English textbooks using Critical Analysis with Visual Grammar Theory. The findings indicate that 1) in the frequency of appearance of men and women, it shows that, overall, female characters are more common than male characters, female characters are more than male with a proportion of 57.3% (70) compared to 42.7% (52 images). 2) In the socio-cultural context, the frequency of appearance of men and women is somewhat different, the frequency of appearance of female characters is more than men in the context of education, family and leisure, male characters are more than women only in the context of work. 3) Gender stereotypes are still found in this textbook, although there are more female characters than men, women are still associated with their gender stereotypes. Therefore, the textbook entitled English describes female characters more than women in terms of the ratio of their appearance and also in the ratio of the four socio-cultural contexts, but female stereotypes still appear in this textbook.